Monodisperse Core-Shell NaYF4:Yb3+/Er3+@NaYF4:Nd3+-PEG-GGGRGDSGGGY-NH2 Nanoparticles Excitable at 808 and 980 nm: Design, Surface Engineering, and Application in Life Sciences - Kostiv, Uliana; Engstová, Hana; Krajnik, Bartosz; Šlouf, Miroslav; Proks, Vladimír; Podhorodecki, Artur; Ježek, Petr; Horák, Daniel (Frontiers in Chemistry, 2020)
Lanthanide-doped upconversion nanoparticles (UCNPs) have a unique capability of upconverting near-infrared (NIR) excitation into ultraviolet, visible, and NIR emission. Conventional UCNPs composed of NaYF4:Yb3+/Er3+(Tm3+) are excited by NIR light at 980 nm, where undesirable absorption by water can cause overheating or damage of living tissues and reduce nanoparticle luminescence. Incorporation of Nd3+ ions into the UCNP lattice shifts the excitation wavelength to 808 nm, where absorption of water is minimal. Herein, core-shell NaYF4:Yb3+/Er3+@NaYF4:Nd3+ nanoparticles, which are doubly doped by sensitizers (Yb3+ and Nd3+) and an activator (Er3+) in the host NaYF4 matrix, were synthesized by high-temperature coprecipitation of lanthanide chlorides in the presence of oleic acid as a stabilizer. Uniform core (24 nm) and core-shell particles with tunable shell thickness (~0.5-4 nm) were thoroughly characterized by transmission electron microscopy (TEM), energy-dispersive analysis, selected area electron diffraction, and photoluminescence emission spectra at 808 and 980 nm excitation. To ensure dispersibility of the particles in biologically relevant media, they were coated by in-house synthesized poly(ethylene glycol) (PEG)-neridronate terminated with an alkyne (Alk). The stability of the NaYF4:Yb3+/Er3+@NaYF4:Nd3+-PEG-Alk nanoparticles in water or 0.01 M PBS and the presence of PEG on the surface were determined by dynamic light scattering, ζ-potential measurements, thermogravimetric analysis, and FTIR spectroscopy. Finally, the adhesive azidopentanoyl-modified GGGRGDSGGGY-NH2 (RGDS) peptide was immobilized on the NaYF4:Yb3+/Er3+@NaYF4:Nd3+-PEG-Alk particles via Cu(I)-catalyzed azide-alkyne cycloaddition. The toxicity of the unmodified core-shell NaYF4:Yb3+/Er3+@NaYF4:Nd3+, NaYF4:Yb3+/Er3+@NaYF4:Nd3+-PEG-Alk, and NaYF4:Yb3+/Er3+@NaYF4:Nd3+-PEG-RGDS nanoparticles on both Hep-G2 and HeLa cells was determined, confirming no adverse effect on their survival and proliferation. The interaction of the nanoparticles with Hep-G2 cells was monitored by confocal microscopy at both 808 and 980 nm excitation. The NaYF4:Yb3+/Er3+@NaYF4:Nd3+-PEG-RGDS nanoparticles were localized on the cell membranes due to specific binding of the RGDS peptide to integrins, in contrast to the NaYF4:Yb3+/Er3+@NaYF4:Nd3+-PEG-Alk particles, which were not engulfed by the cells. The NaYF4:Yb3+/Er3+@NaYF4:Nd3+-PEG-RGDS nanoparticles thus appear to be promising as a new noninvasive probe for specific bioimaging of cells and tissues. This development makes the nanoparticles useful for diagnostic and/or, after immobilization of a bioactive compound, even theranostic applications in the treatment of various fatal diseases.